Utilization of Moringa Leaves to Improve the Quality of Orchid Explants Through Tissue Culture Techniques - Mardiana, Yushi; Sumarji, Sumarji (Prosiding Seminar; 2021: 2021 International Conference of Interdisciplinary SciencesDO - 10.32503/prosidingseminar.v0i0.40, 2021)
Moringa (Moringa oleifera) is a tropical plant that grows and develops in tropical areas such as Indonesia. The use of Moringa plants in Indonesia is currently still limited. One of the ingredients in Moringa leaves is zeatin. This study aims to determine the effect of adding organic matter of Moringa leaf extract to tissue culture media on the growth of orchids. The research was conducted at the Orchid Plant Tissue Culture Laboratory, PT. Archipelago Orchid Award, Sumber Petung Hamlet, Sempu Village, Ngancar District, Kediri Regency, East Java. The research was carried out from November 2018 to January 2019. The research method used was an experimental method in the laboratory, using a Completely Randomized Design with two factors, the first factor is the basic type of media, namely MS media (M1) and VW media (M2). The second factor is the addition of the concentration of Moringa leaf extract, namely K1 = 0 grams of Moringa leaf extract, K2 = 50 grams of Moringa leaf extract, K3 = 100 grams of Moringa leaf extract, K4 = 150 grams of Moringa leaf extract, K5 = 200 grams of Moringa leaf extract. Based on these treatments, 10 treatment combinations were obtained. The experiment was repeated 3 times, then each replication consisted of 4 samples, so there were 120 bottles. Each bottle contains 1 explant. Parameters observed were the percentage of live explants, contamination, and browning. In addition, observations were also made on the number of shoots, number of leaves, plantlet height, and number of roots. The results showed that the addition of Moringa leaf extract to the basic tissue culture media affected the growth of Dendrobium orchid explants. The addition of 150 g/l Moringa leaf extract on VW base media showed the best results in the number of shoots, plant height, and number of roots.